Drug utilization patterns and adherence in patients on systemic and topical medications for the treatment of acne vulgaris - Kher, Mohit; Nuzhat, Qudsia; Passi, Shanta (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Acne vulgaris is a chronic inflammatory condition of the pilosebaceous units, often causing psychosocial distress and posing a treatment challenge due to poor medication adherence. This study aimed to assess drug utilization patterns and adherence among acne vulgaris patients in a tertiary care teaching hospital. Methods: A prospective cross-sectional study was conducted in the Dermatology Department, in collaboration with the Pharmacology Department, ESIC Medical College and Hospital, Faridabad. A total of 296 prescriptions were collected between November 2022 and July 2023. Patients aged 15–35 years with all grades of acne on treatment for at least six months were included; pregnant women and those with hypertension or diabetes were excluded. Drug use patterns and adherence were analyzed. Results: Across 296 prescriptions, 852 drugs were prescribed (294 oral, 558 topical), averaging 2.87 drugs per prescription. Fixed-dose combinations were used in 210 cases, and polypharmacy was observed in 92.56% of prescriptions. Doxycycline (68.1%) was the most common oral drug, while salicylic acid + glycolic acid (47.6%) and clindamycin + retinoic acid (33.4%) were common topicals. Grade I acne predominated in topical-only users, while grade II was more common in those on combination therapy. Combination therapy showed better adherence (74 versus 67 days), improved clinical outcomes (lower IGA scores), stronger patient-doctor relationships (higher PDDR scores), and more favorable skin pH. Conclusions: Combination therapy is commonly used for moderate acne and is associated with improved adherence, clinical outcomes, and patient engagement, highlighting the benefits of integrated treatment approaches.